2014
DOI: 10.1212/wnl.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Small strokes causing severe vertigo

Abstract: Small strokes affecting central vestibular projections can present with isolated AVS. The HINTS "plus" hearing battery identifies these patients with greater accuracy than early MRI-DWI, which is falsely negative in half, up to 48 hours after onset. We found nonlacunar mechanisms in half, suggesting greater risk than might otherwise be assumed for patients with such small infarctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(173 citation statements)
references
References 22 publications
10
150
0
13
Order By: Relevance
“…This forms the basis of the 'HINTS' protocol (Head-impulse, Nystagmus, Test-skew) which has at least as much sensitivity to rule out posterior fossa stroke as MRI does. 5,6 Additional brainstem VOR mechanisms The VOR is under powerful cerebellar control and this is reviewed by Zee in this issue. Indeed many 'cerebellar' eye signs are actually vestibulo-cerebellar signs, including the common syndrome of downbeat nystagmus.…”
Section: Basic Clinical Anatomy Of the Vormentioning
confidence: 99%
“…This forms the basis of the 'HINTS' protocol (Head-impulse, Nystagmus, Test-skew) which has at least as much sensitivity to rule out posterior fossa stroke as MRI does. 5,6 Additional brainstem VOR mechanisms The VOR is under powerful cerebellar control and this is reviewed by Zee in this issue. Indeed many 'cerebellar' eye signs are actually vestibulo-cerebellar signs, including the common syndrome of downbeat nystagmus.…”
Section: Basic Clinical Anatomy Of the Vormentioning
confidence: 99%
“…Focal lesion in the cortical or subcortical as well as brainstem or cerebellum is the most common causes of central AVS [1][2][3][4]10,11,15], but brain ischemia, hypoxia, poisoning, metabolic disorder, and malnutrition is also the factors of brain dysfunction caused by the lesions of vestibular central pathways [5][6][7][8][9][12][13][14]16].…”
Section: Discussionmentioning
confidence: 99%
“…There are many reasons for central AVS. The most common causes are acute ischemic stroke [1,2], followed by spontaneous intra cerebral hemorrhage [1,3]. Perhaps, there are many other well-known reasons for the first symptom that commonly precipitate central AVS, such as migraineous vertigo [4], heart disease [5], acute drug poisoning or adverse reactions (including carbon monoxide, phenytoin, antihypertensive drugs and antitumor drugs) [6][7][8][9], vertigo epilepsy [10], and multiple sclerosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…50% of patients with a stroke who present with isolated vertigo will have a falsely negative MRI up to 48 hours after onset. 25 A recent article by Simonsen et al found DWI negative strokes were twice as likely in the posterior circulation (34% vs 15%), but the sensitivity of DWI seems variable within the literature. 31,32 The sensitivity of MRI increases with time from symptom onset to imaging.…”
Section: Special Topics In Imaging Of Bao and Posterior Fossamentioning
confidence: 99%